Lettuce and arugula production in intercropping and organic fertilization - Ribera, Laura M. [UNESP]; Filho, Arthur B. Cecilio [UNESP]; Peres, Nathalia D.; Santana, Dthenifer C. [UNESP]; da Silva, Maiele L. (FapUNIFESP (SciELO), 2023)
Compared to monoculture, vegetable intercropping allows the optimization of environmental resources and inputs, with positive effects on the yield and profitability of the crop. This study aimed to evaluate the yield of lettuce and arugula in intercropping and intercrop evaluation indexes according to cattle manure doses. The experiment was conducted in Aquidauana, MS, Brazil. Five doses of cattle manure (0, 15, 30, 45, and 60 t ha-1) were evaluated with four replications in a randomized block design. Higher growth and yield of the intercropped species were observed when the intercrop received 60 t ha-1 of cattle manure. However, the maximum values of the variables were not reached, so better performances can be obtained with higher doses. The indexes of actual yield loss and advantage of intercropping presented higher values starting at doses of 26 and 30 t ha-1 of manure, respectively. The highest land use efficiency (1.28) was obtained with 60 t ha-1 of cattle manure, indicating the agronomic viability of the lettuce and arugula intercrop when fertilized only with cattle manure.
Produção de alface e rúcula em cultivo consorciado e adubação orgânica
Keywords: Agronomic performance; Cultivation systems; Eruca sativa L; Lactuca sativa L